Accuracy Comparison of the Optical 3D Scanner and CT Scanner - Mendricky, Radomir; Sobotka, Jiri (Manufacturing Technology Journal, 2020)
During the last years, due to the dynamic development of the non-contact measurement methods, there has been observed still increasing number of their applications in various fields - not only in the engineering industry. E.g. from the dimensional quality point of view, knowledge of real 3D data of a given part is truly very important. There are several options for obtaining these data such as the usage of optical 3D digitization or computed tomography (CT). However, within the mutual comparability of such data, it is very important to know not only the accuracy of acquiring 3D data, but also e.g. possibilities of these systems in terms of own measurement. In the paper, a specially designed part containing various convex and concave shapes was measured by using two different systems (ATOS TripleScan optical 3D scanner and METROTOM 1500 G2 CT scanner). The resulting scanned models were then compared not only in terms of dimensional accuracy, but also in terms of quality and detail of the obtained data or the time required to prepare the measurement and its implementation.
Keywords: 3D Digitalization; Computed Tomography; Optical 3D Scanning; CMM; Inspection